FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN MAHASISWA PROGRAM STUDI S1 AGRIBISNIS UNIVERSITAS DIPONEGORO UNTUK BERWIRAUSAHA DI BIDANG PERTANIAN - Nabila Azima Putri; Siwi Gayatri; Kadhung Prayoga (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2022)
The number of students of the Bachelor Agribusiness Study Program who have done entrepreneurship is currently known to be only around 2%. Agribusiness bachelor student's decision to become entrepreneurs are affected by several factors, including motivation, family environment, and capital. This study aims to analyze the factors that affected the decision of agribusiness bachelor students to become entrepreneurs. The method used was a 96 respondents survey method. The datas were analyzed by binary logistic regression. The results of binary regression analysis show that the independent variables simultaneously have a significant effect on the dependent variables. Partially, the family environment and capital variables affect the decision of the class of 2017 Agribusiness Study Program students to become entrepreneurs in the agricultural sector. In the other hand, motivation does not affected their decision to become entrepreneurs. To increase the number of agribusiness bachelor students in entrepreneurship, the study program is expected to be able to work together with the university to provide real entrepreneurship experience for students by increasing the quota of participants for entrepreneurial programs such as the Student Entrepreneurship Program (PMW), Entrepreneurship Student Creativity (PKM-K) and Merdeka Belajar Kampus Merdeka (MBKM).